Study of thallium iodide dissolution kinetics in aqueous sodium iodide solutions in production conditions - Babich, G.A.; Blank, A.B.; Kisil', E.P.; Filippovich, L.I. (Functional Materials, 2006)
The kinetics of thallium iodide dissolution in sodium iodide solutions at concentration of the latter ranging from 0.6 to 6.3 mol/dm³ has been investigated. An essential time-depended variation of thallium iodide dissolution rate has been established. Consideration of thallium iodide solubility dependence on sodium iodide concentration under varying eхperimental conditions has evidenced the presence of two parallel processes. The first is an equilibrium one and is connected with formation of thallium ion compleх with iodide ions. The second process is non-equilibrium one and is due to interaction with iodine. Вивчено кiнетику розчинення iодиду талiю у розчинах iодиду натрiю, концентрацiя яких змiнювалася вiд 0,6 До 6,3 моль/дм³. Встановлено суттєве змiнення швидкостi розчинення iодиду талiю за часом. Вивчення кривих залежностi розчинностi iодиду талiю вiд концентрацiї iодиду натрiю при варiюваннi умов експерименту дозволило виявити наявнiсть двох процесiв, що протiкають паралельно: рiвноважного, пов'язаного з комплексоутворенням iонiв талiю з iодид-iонами, а також нерiвноважного, обумовленого взаемодiєю з iодом. Изучена кинетика растворения иодида таллия в растворах иодида натрия, концентрация которых изменялась от 0,6 До 6,3 моль/дм³. Установлено существенное изменение скорости растворения иодида таллия во времени. Изучение кривых зависимости растворимости иодида таллия от концентрации иодида натрия при варьировании условий эксперимента позволило обнаружить наличие двух параллельно протекающих процессов: равновесного, связанного с комплексообразованием ионов таллия с иодид-ионами, а также неравновесного, обусловленного взаимодействием с иодом.